Rosmarinic Acid Suppresses Abdominal Aortic Aneurysm Progression in Apolipoprotein E-deficient Mice - Bian, Huimiao; Wang, Yang; Wu, Peng; Han, Na; Wang, Linlin; Li, Xue; Zhang, XianJing; Cho, Kenka; Zhang, Yongyu; Yin, Jun; Jiang, Baohong (Planta Medica, 2021)
An abdominal aortic aneurysm is a life-threatening cardiovascular disorder caused by dissection and rupture. No effective medicine is currently available for the > 90% of patients whose aneurysms are below the surgical threshold. The present study investigated the impact of rosmarinic acid, salvianolic acid C, or salvianolic acid B on experimental abdominal aortic aneurysms. Abdominal aortic aneurysms were induced in apolipoprotein E-deficient mice via infusion of angiotensin II for 4 wks. Rosmarinic acid, salvianolic acid C, salvianolic acid B, or doxycycline as a positive control was provided daily through intraperitoneal injection. Administration of rosmarinic acid was found to decrease the thickness of the aortic wall, as determined by histopathological assay. Rosmarinic acid also exhibited protection against elastin fragmentation in aortic media and down-regulated cell apoptosis and proliferation in the aortic adventitia. Infiltration of macrophages, T lymphocytes, and neutrophils in aortic aneurysms was found, especially at the aortic adventitia. Rosmarinic acid, salvianolic acid C, or salvianolic acid B inhibited the infiltration on macrophages specifically, but these compounds did not influence T lymphocytes and neutrophils. Expression of matrix metalloproteinase 9 and macrophage migration inhibitory factor significantly increased in aortic aneurysms. Rosmarinic acid and salvianolic acid C decreased the expression of matrix metalloproteinase-9 in media, and rosmarinic acid also tended to reduce migration inhibitory factor expression. Further then, partial least squares-discriminate analysis was used to classify metabolic changes among different treatments. Rosmarinic acid affected most of the metabolites in the biosynthesis of the citrate cycle, fatty acid pathway significantly. Our present study on mice demonstrated that rosmarinic acid inhibited multiple pathological processes, which were the key features important in abdominal aortic aneurysm formation. Further study on rosmarinic acid, the novel candidate for aneurysmal therapy, should be undertaken to determine its potential for clinical use.
Keywords: abdominal aortic aneurysm; rosmarinic acid; salvianolic acid C; salvianolic acid B; Salvia miltiorrhiza Bunge; Labiatae